Individually together : volunteering in late modernity: social work in the Finnish church - Yeung, Anne Birgitta; Sosiaali- ja terveysturvan keskusliitto (Finnish Federation for Social Welfare and Health, 2004)
Summary (s. 13-17).
Keywords: vapaaehtoistyö : kirkko; evankelis-luterilainen kirkko; sosiaalityö